Prospective study of Clostridium difficile intestinal colonization and disease following single-dose antibiotic prophylaxis in surgery. - Privitera, G (1991)
A total of 108 volunteers undergoing an elective surgical procedure were randomly given a single 2-g intravenous prophylactic dose of either a cephalosporin or mezlocillin. Stool samples were cultured for Clostridium difficile the day before the operation and later on postoperative days 4, 7, and 14. C. difficile was detected in 23.0% of patients who received a cephalosporin (cefoxitin, 8.3%; cefazolin, 14.3%; cefotetan, 20.0%; ceftriaxone, 25.0%; cefoperazone, 43.7%), in 3.3% of patients given mezlocillin, and in none of 15 control volunteers given no antimicrobial agent. No patient experienced diarrhea.